2015
DOI: 10.1038/srep09944
|View full text |Cite
|
Sign up to set email alerts
|

Citric Acid Enhanced Copper Removal by a Novel Multi-amines Decorated Resin

Abstract: Cu removal by a novel multi-amines decorated resin (PAMD) from wastewater in the absence or presence of citric acid (CA) was examined. Adsorption capacity of Cu onto PAMD markedly increased by 186% to 5.07 mmol/g in the presence of CA, up to 7 times of that onto four commercial resins under the same conditions. Preloaded and kinetic studies demonstrated adsorption of [Cu-CA] complex instead of CA site-bridging and variations of adsorbate species were qualitatively illustrated. The interaction configuration was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 54 publications
1
27
2
Order By: Relevance
“…For the HPC, the peak appearance at 1597 and 1416 cm -1 is due to COO -antisymmetric and symmetric stretching, respectively, suggesting the binding of potassium with COO - [41,42]. The functional group of COO -K + could be originated from the carboxylate of citric acid coordinated to Cu after the formation of KCuHCF, and the presence of Cu-CA complex in the CPC is confirmed by the shoulder peak at 1621 cm -1 [43]. In addition, the distinct bands at 2089, 586, and 478 cm -1 in the HPC clearly demonstrate the existence of KCuHCF, where the shift of C N stretching compared to that of the bulk KCuHCF is related to the internal strain in the film matrix [44].…”
Section: Characterization: Chemical Propertiesmentioning
confidence: 78%
“…For the HPC, the peak appearance at 1597 and 1416 cm -1 is due to COO -antisymmetric and symmetric stretching, respectively, suggesting the binding of potassium with COO - [41,42]. The functional group of COO -K + could be originated from the carboxylate of citric acid coordinated to Cu after the formation of KCuHCF, and the presence of Cu-CA complex in the CPC is confirmed by the shoulder peak at 1621 cm -1 [43]. In addition, the distinct bands at 2089, 586, and 478 cm -1 in the HPC clearly demonstrate the existence of KCuHCF, where the shift of C N stretching compared to that of the bulk KCuHCF is related to the internal strain in the film matrix [44].…”
Section: Characterization: Chemical Propertiesmentioning
confidence: 78%
“…The biochar is chemically stable and has a highly porous structure 15 . According to previous research, biochar is very suitable as adsorbents in environment management over adsorption processes 16 , 17 ; and has been used for the removal of pollutants from soil or water for decades. However, the studies about immobilizing laccase on biochar have been seldom reported.…”
Section: Introductionmentioning
confidence: 99%
“…The ion exchange resins, which are widely‐used for the removal of heavy metal ions from water. Their adsorption capacity of Cu II is reported to be between 100 and 200 mg g ‐1 , whilst for the case of Co II the values range between 40 and 90 mg g ‐1 ,. Various surface oxidized carbon materials are also known as adsorbents of copper ions.…”
Section: Resultsmentioning
confidence: 99%